Likelihood of cesarean delivery after applying leading active labor diagnostic guidelines. Issue 2 (15th February 2017) - Neal, Jeremy L.; Lowe, Nancy K.; Phillippi, Julia C.; Ryan, Sharon L.; Knupp, Amy M.; Dietrich, Mary S.; Thung, Stephen F.
Abstract: Background: Friedman, the United Kingdom's National Institute for Health and Care Excellence (NICE), and the American College of Obstetricians and Gynecologists/Society for Maternal‐Fetal Medicine (ACOG/SMFM) support different active labor diagnostic guidelines. Our aims were to compare likelihoods for cesarean delivery among women admitted before vs in active labor by diagnostic guideline (within‐guideline comparisons) and between women admitted in active labor per one or more of the guidelines (between‐guideline comparisons). Design: Active labor diagnostic guidelines were retrospectively applied to cervical examination data from nulliparous women with spontaneous labor onset (n = 2573). Generalized linear models were used to determine outcome likelihoods within‐ and between‐guideline groups. Results: At admission, 15.7%, 48.3%, and 10.1% of nulliparous women were in active labor per Friedman, NICE, and ACOG/SMFM diagnostic guidelines, respectively. Cesarean delivery was more likely among women admitted before vs in active labor per the Friedman (AOR 1.75 [95% CI 1.08‐2.82] or NICE guideline (AOR 2.55 [95% CI 1.84‐3.53]). Between guidelines, cesarean delivery was less likely among women admitted in active labor per the NICE guideline, as compared with the ACOG/SMFM guideline (AOR 0.55 [95% CI 0.35‐0.88]). Conclusion: Many nulliparous women are admitted to the hospital before active labor onset. These women are significantly more likely to have a cesarean delivery. Diagnosing active labor before admission or before intervention to speed labor may be one component of a multi‐faceted approach to decreasing the primary cesarean rate in the United States. The NICE diagnostic guideline is more inclusive than Friedman or ACOG/SMFM guidelines and its use may be the most clinically useful for safely lowering cesarean rates.